Metaphor of Covid-19 in Kompas Daily as a Means of Learning Indonesian Language of PGSD Students - Sasti, Poetri Mardiana (Widyagogik, 2023)
The objective of this study is to describe the type of conceptual metaphor in Covid-19 news in Kompas daily between December 2021 to February 2022. This research is qualitative research using semantic and cognitive approaches. A semantic approach is used to parse linguistic units in metaphorical expressions. Meanwhile, cognitive approaches are used to parse the conceptualization of metaphors. The data collected with documentation, observation, and note taking. The observation was carried out by examine at news related to Covid-19 using metaphorical expressions. The note taking technique carried out by writing down the metaphorical expressions used in Covid-19 news in Kompas daily. Data analysis was carried out using the matching method followed by technique of critical element segment and technique of same interrelational. The technique of critical element segment is used to determine the lingual elements in metaphorical expressions. Meanwhile, the technique of same interrelational is used to determine the correspondence of the source domain of metaphorical expressions. The results of this study show that in the Covid-19 news in Kompas daily from December 2021 to February 2022, three types of conceptual metaphors were found that are often used by journalists. The three metaphors include ontological metaphors, structural metaphors, and orientational metaphors.